2006
DOI: 10.1111/j.1467-8535.2006.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Spelling and grammar checkers: are they intrusive?

Abstract: Spelling and grammar checkers help to make surface errors more apparent; do they influence the way in which people revise the content of their writing? We investigated whether the presence of checkers distracts students from making content revisions. Twenty-five freshmen, 20 English majors and 20 graduate students revised two essays on a computer, one with the spelling and grammar checkers, and the other with a dictionary. These essays were unfamiliar to the students and rigged with content and surface errors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
11
0
7
Order By: Relevance
“…The limited functionality and intrusive effect of MS spelling and grammar/style checkers have been critiqued by several authors (Vernon 2000), as have their ideological and pedagogical implications (McGee and Ericsson 2002), including their potential for foregrounding surface corrections over more meaningful revisions (Buck 2008). Against this are studies such as that by Figueredo and Varnhagen (2006), who found that use of these tools during the revision process increased the number and accuracy of surface corrections, while not impacting negatively on content revisions. 7 While recognising the limitations of built-in word-processing tools, we concur with scholars who advocate their place in the writing classroom (Potter and Fuller 2008), in one-toone writing tutorials (Buck 2008) and when giving written feedback on student drafts (Stapleton and Radia 2010).…”
Section: Use Of Software Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited functionality and intrusive effect of MS spelling and grammar/style checkers have been critiqued by several authors (Vernon 2000), as have their ideological and pedagogical implications (McGee and Ericsson 2002), including their potential for foregrounding surface corrections over more meaningful revisions (Buck 2008). Against this are studies such as that by Figueredo and Varnhagen (2006), who found that use of these tools during the revision process increased the number and accuracy of surface corrections, while not impacting negatively on content revisions. 7 While recognising the limitations of built-in word-processing tools, we concur with scholars who advocate their place in the writing classroom (Potter and Fuller 2008), in one-toone writing tutorials (Buck 2008) and when giving written feedback on student drafts (Stapleton and Radia 2010).…”
Section: Use Of Software Toolsmentioning
confidence: 99%
“…However, the topic continues to be of interest to teachers of academic writing. The ongoing development of grammar/style and spelling checkers has prompted several scholars to revisit these tools and their pedagogic uses (Buck 2008, Figueredo and Varnhagen 2006, McGee and Ericsson 2002, Potter and Fuller 2008, Vernon 2000. Investigations which compare the processes of composing by hand or on a computer explore their respective effects on the cognitive process (Medimorec and Risko 2016), early writing outcomes (Wollscheid, Sjaastad and Tømte 2016), and the implications for time-constrained assessments (Hunsu 2015, Mogey and Fluck 2015, Whithaus, Harrison and Midyette 2008.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Figueredo and Varnhagen (2006) conducted a study on the use of computer in teaching writing. By using computers, students were able to correct mistakes with the aid of spelling and grammar checkers.…”
Section: Introductionmentioning
confidence: 99%
“…Because Varnhagen (2004, 2006) did not assess the students in this area, they could have missed an important element explaining the student's lack of vigilance while detecting errors. The detection of spelling errors, regardless of the format is generally difficult for spellers mainly because of their reduced attention to the task (Figueredo & Varnhagen, 2006;Longcamp et al, 2005). An alternate explanation is that by relying mostly on the visual features of a word to discriminate between misspellings and correct word spellings, participants seemingly process strings of letters without integrating other word qualities (phonological and orthographic codes).…”
Section: Discussionmentioning
confidence: 99%
“…It was understood that spelling recognition processes can be difficult, mainly in terms of the attentional resources required to process the word's meaning (Figueredo & Varnhagen, 2006;Rees & Russell, 1999) and not necessarily in regard to spelling abilities (i.e., orthographic knowledge). In this way, the influence of format on the spelling tasks became evident when the cognitive load increased, and when spellers switched working formats to conduct the tasks (i.e., from printing to keyboarding or from keyboarding to printing).…”
Section: Spellers' Accuracymentioning
confidence: 99%